TSPO Ligands PK11195 and Midazolam Reduce NLRP3 Inflammasome Activation and Proinflammatory Cytokine Release in BV-2 Cells - Feng, Hao; Liu, Yongxin; Zhang, Rui; Liang, Yingxia; Sun, Lina; Lan, Nannan; Ma, Baoyu (Frontiers in Cellular Neuroscience, 2020)
Neuroinflammation related to microglial activation plays an important role in neurodegenerative diseases. The Translocator Protein 18 kDa (TSPO) ligands reduce neuroinflammation in neurodegeneration disease as value therapeutic targets for inflammation associated neurologic diseases. Therefore, we explore whether TPSO ligands exert an anti-inflammatory effect by affecting the (nucleotide binding domain-like receptor protein 3) NLRP3 inflammasome and thereby inhibiting the release of inflammatory cytokines. In the present study, BV-2 cells were exposed to lipopolysaccharide (LPS) for 6 hours to induce inflammatory response. We found that the levels of reactive oxygen species (ROS), NLRP3 inflammasome, interleukin-1β (IL-1β) and interleukin-18 (IL-18) were significantly increased by LPS stimulation. However, pretreatment with TSPO ligands inhibit BV-2 microglial activation and significantly reduce the expression of ROS, NLRP3 inflammasome, IL-1β and IL-18. Collectively, these results indicate that TSOP ligand is a promising target to control microglial reactivity and neuroinflammatory diseases.